Sabhāparva : prastāvanā, mūḷa, pāṭhabheda, ṭīpā, spashṭīkaraṇa, ityād̃īsaha - Mukteśvara, 1608-1660 (SAMP early 20th-century Indian books project, 1949)
Verse work based on episodes from Mahābhārata; with critical introduction and explanatory notes.